Pelatihan Penyulingan Minyak Atsiri Berbahan Rempah Khas Nusantara - Muhammad Akmal Rizqullah; Muhammad Khusunul Khairu; Harlinda Kuspradini (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2022)
Herbs and Spices are the main wealth of Indonesia which has indeed been known throughout the world. Many countries even import these crops from Indonesia. Spices are a type of plant that has a strong taste and aroma and functions as a spice and flavor enhancer in food. In addition to being used in cooking, spices can also be used as medicines as well as raw materials for herbal medicine. Another form of utilization of these spices is the taking of essential oils found in these spices. This utilization is part of the development of diversification of natural products. The processing of spices into essential oils is one of the other uses with various benefits, as an essential oil, namely an antidote to diseases and other benefits for the health of the human body, and also as an exterminator of several pests and insects. Essential oil processing can be done simply by various groups of people. However, there are still many people who do not know how to properly process essential oils. This Student Service activity is a form of knowledge transfer by the implementing team from the Forest Products Chemistry and Renewable Energy Laboratory, Faculty of Forestry, Mulawarman University, regarding the processing of essential oils and the various properties or benefits of essential oils made from indonesian spices in the hope of increasing the skills of students or the younger generation in processing essential oils and motivating them to open essential oil-based business opportunities from natural ingredients.